Pharmacokinetics and Tolerability of Factor XIII Concentrates Prepared from Human Placenta or Plasma: a Crossover Randomised Study - Brackmann, H H; Egbring, R; Ferster, A; Fondu, P; Girardel, J M; Kreuz, W; Masure, R; Miloszewski, K; Stibbe, J; Zimmermann, R; Krzensk, U; Hoos, A (Thrombosis and Haemostasis, 1995)
The pharmacokinetics and tolerability of factor XIII (FXIII) from plasma were compared with those of FXIII from placenta in a randomised, double-blind, crossover study involving 13 patients with congenital FXIII deficiency. Both FXIII activity and FXIII antigen were monitored. No difference was seen in the mean half-lives of the two preparations (9.3 days and 9.1 days for plasma and placenta FXIII activity, respectively). Response was similar for both preparations, but was slightly greater for FXIII from plasma.Similar results were found for recovery (65% vs 60%). The area under the data completed by extrapolation was significantly higher for FXIII from plasma. No differences between preparations in terms of efficacy or tolerability were observed. It can be concluded that treatment with FXIII concentrate from plasma is as efficient as with FXIII concentrate from placenta in terms of recovery and half-life. Both preparations were equivalent in terms of safety during the observation period. With the administration of monthly injections of approximately 30 U/kg serious bleeding events were prevented and no other serious adverse events occurred.